2021
DOI: 10.1155/2021/6656732
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Rainfall Distribution of Soan River Basin, Pothwar Region, Pakistan

Abstract: This study evaluates the spatiotemporal rainfall variability over the semimountainous Soan River Basin (SRB) of sub-Himalayan Pothwar region, Pakistan. The temporal rainfall trend analysis of sixteen rain gauges was performed on annual basis with long-term (1981–2016) data. The results depicted that there is substantial year-to-year and season-to-season variability in rainfall patterns, and rainfall patterns are generally erratic in nature. The results highlight that most of the highland rainfall stations show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…It could possibly be linked to the geographical aspect of the area, where the nearly-steep slope has isolated itself from continued interaction. These results are matched with the findings of Padmakumar et al [28]; however, the reports of Phillips et al [45] offer a visible challenge. One of the possible reasons for such a pattern is the presence of fewer but larger diameter trees at higher elevation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It could possibly be linked to the geographical aspect of the area, where the nearly-steep slope has isolated itself from continued interaction. These results are matched with the findings of Padmakumar et al [28]; however, the reports of Phillips et al [45] offer a visible challenge. One of the possible reasons for such a pattern is the presence of fewer but larger diameter trees at higher elevation.…”
Section: Discussionsupporting
confidence: 88%
“…Temperatures range from −22 • C in winter in the north to 50 • C in summer in the south. The precipitation is 1500-2000 mm and 100-200 mm across the north and south of Pakistan, respectively [45]. Pakistan is also going to face the brunt of climate change due to its hydrological reserve's shrinkage, rapid glacier melting floods, and droughts [43].…”
Section: Study Areamentioning
confidence: 99%
“…We found that overall NEX-GDDP GCMs performed better over Dhoke Pathan sub catchment than over the Chirah sub catchment. This might be attributed to different catchment characteristics, for instance, the Dhoke Pathan sub catchment is nineteen times the size of the Chirah sub catchment, also the Chirah sub catchment is mostly dominated by humid and subhumid climates, while the Dhoke Pathan sub catchment, on the other hand, is dominated by arid and semi-arid climates [17]. Overall, we found that uncertainties related to hydrological and climate models are dependent on the climatic conditions of the studied region, similar findings were reported by other studies as well [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Slightly more than fifty percent of the region has flat to gentle slopes, more than twenty percent is comprised of medium slope, and the remaining area has either steep or very steep slopes. Humid and subhumid climates dominate the northern part of the SRB, while southern regions are dominated by arid and semiarid climates [17].…”
Section: Study Areamentioning
confidence: 99%
“…Pakistan, in lieu of being located in South Asia is projected to be one of the most vulnerable and worst hit counties by the dire consequences of climate change, reasons being the geographical features and reliance on agriculture and natural resources for livelihoods (Islam, Sultan and Afroz, 2009). Water distribution and consumption predominantly relies on monsoonal rainfall, but the natural rain is unevenly distributed in time and space resulting in oods due to erratic rainfall in one region while drought in another region of the country (Hussain, Nabi and Wu, 2021).…”
Section: Introductionmentioning
confidence: 99%